Analysis of Students Basic Teaching Skills on Teaching Practice of Micro-Teaching Courses - Kusmiyati; Merta, I Wayan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Basic teaching skills are skills that prospective teacher students must have. This research aims to determine the level of basic teaching skills in teaching practice among Biology Education students taking the Micro Teaching course in class A group B in 2022/2023. Data was collected from observations of student teaching practices through peer teaching. The instrument used is an observation sheet derived from indicators of eight aspects of basic teaching skills, with answer choices using a Likert scale. The data was analyzed descriptively by calculating the average score obtained by each indicator on the eight aspects of basic teaching skills observed. The observation results show that students' average in all aspects of basic teaching skills is very good. In contrast, the results of observations on the indicators for each element of skills show categories that vary from quite good, good, and very good. It can be concluded that students have been able to apply the eight aspects of basic teaching skills in teaching practice very well. However, if we look at the indicators for each aspect of skills, there are still students in the quite good and good categories.